2021
DOI: 10.1101/2021.10.25.465732
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Constructing the hierarchy of predictive auditory sequences in the marmoset brain

Abstract: Our brains constantly generate predictions of sensory input that are compared with actual inputs, propagate the prediction-errors through a hierarchy of brain regions, and subsequently update the internal predictions of the world. However, the essential feature of predictive coding, the notion of hierarchical depth and its neural mechanisms, remains largely unexplored. Here, we investigated the hierarchical depth of predictive auditory processing by combining functional magnetic resonance imaging (fMRI) and hi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 41 publications
3
6
0
Order By: Relevance
“…Consistent with the well-known auditory pathway in marmosets (34) and a recent fMRI study in marmosets (35), we found auditory responses in the inferior colliculus and medial geniculate nucleus. Interestingly, the inferior colliculus, medial geniculate nucleus, pulvinar, amygdala, caudate and putamen also showed larger activations for vocalizations.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with the well-known auditory pathway in marmosets (34) and a recent fMRI study in marmosets (35), we found auditory responses in the inferior colliculus and medial geniculate nucleus. Interestingly, the inferior colliculus, medial geniculate nucleus, pulvinar, amygdala, caudate and putamen also showed larger activations for vocalizations.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with this interpretation, several studies have shown transient and spectrally broad-band (i.e. extending well above 100Hz without a narrow-band peak) increases in gamma LFP power for unpredictable as compared to predictable stimuli (Chao et al, 2018;Todorovic et al, 2011;Jiang et al, 2022;Bastos et al, 2020) (see Figure 4A). A recent study has directly dissociated narrow from broad-band spectral energy in marmoset A1 (Figure 2A).…”
Section: The Gamma Rhythm In Predictive Processingsupporting
confidence: 62%
“…The idea that alpha and beta rhythms are involved in FB communication of predictions is primarily based on Grangercausality analyses of field potential data (see next section), rather than their modulation by behavioral or stimulus conditions. Several (but not all, Canales-Johnson et al (2021a); Todorovic et al (2011); Arnal et al (2011)) studies have observed a suppression of alpha/beta-band power for unpredicted stimuli (Bastos et al, 2020;Chao et al, 2018;Jiang et al, 2022;Von Stein et al, 2000) (Figure 4), although these studies did not explicitly detect rhythms and distinguish these from aperi-odic processes (BOX 2). This finding has been interpreted as evidence for a role in FB signalling.…”
Section: Alpha and Beta Rhythms In Predictive Processingmentioning
confidence: 95%
“…Cortical mechanisms of auditory prediction error (PE) have been extensively studied using evoked-related potentials (ERP) and spectral analyses (Canales-Johnson et al, 2021; Blenkmann et al, 2019; Chao et al, 2018; Jiang et al, 2022; Parras et al, 2017). A well-studied ERP marker of auditory PE is the mismatch negativity (MMN), an event-related potential (ERP) that peaks around 150–250 ms after the onset of an infrequent acoustic stimulus (Parras et al, 2017).…”
Section: Resultsmentioning
confidence: 99%